2016
DOI: 10.1249/jes.0000000000000079
|View full text |Cite
|
Sign up to set email alerts
|

Posttranslational Arginylation Regulates Striated Muscle Function

Abstract: In this article, we propose the hypothesis that the posttranslational arginylation of proteins, a process catalyzed by the enzyme arginyl-tRNA-transferase, regulates active and passive force generation in striated muscles. Specifically, we propose that proteins essential for muscle contraction and force production are regulated by arginylation, including myosin heavy chain, troponin, actin, and titin filaments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In the present study, we found reduced PKC activity and improved titin-PEVK site-specific phosphorylation after treatment with the sGC activator, both of which may have contributed to the reduced cardiomyocyte stiffness. Additional posttranslational modifications that alter the stiffness of titin include arginylation (Leite Fde et al, 2016) and various oxidative modifications, such as disulfide bonding (Grutzner et al, 2009;Giganti et al, 2018), S-glutathionylation (Alegre-Cebollada et al, 2014), and sulphenylation (Beedle et al, 2016). Therefore, since the sGC activator reduces oxidative stress, improved cardiomyocyte stiffness could be related, in part, to reduced titin oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found reduced PKC activity and improved titin-PEVK site-specific phosphorylation after treatment with the sGC activator, both of which may have contributed to the reduced cardiomyocyte stiffness. Additional posttranslational modifications that alter the stiffness of titin include arginylation (Leite Fde et al, 2016) and various oxidative modifications, such as disulfide bonding (Grutzner et al, 2009;Giganti et al, 2018), S-glutathionylation (Alegre-Cebollada et al, 2014), and sulphenylation (Beedle et al, 2016). Therefore, since the sGC activator reduces oxidative stress, improved cardiomyocyte stiffness could be related, in part, to reduced titin oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the relevance of titin oxidation in heart disease is largely unknown. Other PTMs (such as arginylation ) may also alter titin‐based passive stiffness and warrant further investigation into the role they may play in both healthy and diseased hearts. Finally, PTMs of titin that alter titin‐based myocardial passive stiffness represent a promising potential target for therapeutic intervention in HF patients with overly stiff hearts (such as in HFpEF), despite recent setbacks in some preclinical studies regarding to the role of cGMP‐PKG activation for myocardial stiffness in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…The fifth site, Asp32535, is present in the Is3 region between Ig domains M4 and M5 in the M-band (321). Similarly, several arginylation sites on titin were discovered in mouse heart lysates residing to Ig domains within its A-band portion and the TK domain in the M-band (320). In particular, Leu7960 resides in the first Ig domain of the seven-domain super repeat, Val15013 in the second Ig domain of the 11-domain super repeat, and Cys24818 in the TK domain (residues correspond to the N2B-titin sequence NP_082280.2).…”
Section: Titin (Aka Connectin)mentioning
confidence: 99%
“…Similarly, isolated myofibrils from a skeletal muscle specific knockout of arginyl-transferase exhibit reduced passive force development (321). Given that titin is the primary regulator of passive force in the sarcomere, it is likely that titin arginylation contributes to the regulation of passive stiffness (320, 321). Since all of the arginylation sites localize to titin’s inextensible region, and not the extensible I-band region, it was further proposed that titin arginylation regulates passive force possibly through modifying its anchorage to the thick filament (320, 321).…”
Section: Titin (Aka Connectin)mentioning
confidence: 99%